Pengaruh Motivasi Kerja dan Lingkungan Kerja Terhadap Kepuasan Kerja Karyawan Divisi Non Produksi PT XYZ - Panggabean, Samuel Marcelino; Frianto, Agus (HORIZON: Indonesian Journal of Multidisciplinary, 2026)
This study aims to analyze the influence of work motivation and work environment on job satisfaction of non-production division employees at PT XYZ. The study used a quantitative approach with a survey design, involving 113 respondents selected through a simple random sampling method. Data were collected using a structured questionnaire and analyzed using multiple linear regression using SPSS version 26. The results of the study indicate that work motivation and work environment have a positive and significant effect on employee job satisfaction, both partially and simultaneously. This indicates that employees with a high level of work motivation and supported by a comfortable, safe, and supportive work environment tend to have a better level of job satisfaction. The implications of this study emphasize the importance of the role of management in designing human resource policies oriented towards increasing work motivation, such as providing rewards, career development opportunities, and performance recognition, as well as creating a conducive work environment physically and psychosocially. By considering these two factors in an integrated manner, the company is expected to be able to increase employee job satisfaction which can ultimately have an impact on improving performance, loyalty, and organizational sustainability.